2020
DOI: 10.1108/ijse-03-2019-0198
|View full text |Cite
|
Sign up to set email alerts
|

Human capital and export performance of small and medium enterprises in Pakistan

Abstract: PurposeThis study examines the influence of human capital, overall and by dimensions, on the export performance of small and medium enterprises (SMEs) in the manufacturing sector of Pakistan. The study also investigates the role of absorptive capacity in the relationship between human capital dimensions and export performance.Design/methodology/approachData from 586 manufacturing sector SMEs were collected for analysis. The study applied covariance-based structural equation modeling (SEM) to estimate the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 73 publications
4
83
0
7
Order By: Relevance
“…Corporate entrepreneurship theory might help provide a more robust explanation for firm performance, which emphasizes the dynamic, often chaotic, aspects of early internationalization where skills, experience and social networks play a dominant role (Ahimbisibwe et al , 2020). Moreover, previous international business studies are viewed as paying insufficient attention to individual importance with their human capital for SMEs internationalization (Mubarik et al , 2020; Oviatt and McDougall, 1994).…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate entrepreneurship theory might help provide a more robust explanation for firm performance, which emphasizes the dynamic, often chaotic, aspects of early internationalization where skills, experience and social networks play a dominant role (Ahimbisibwe et al , 2020). Moreover, previous international business studies are viewed as paying insufficient attention to individual importance with their human capital for SMEs internationalization (Mubarik et al , 2020; Oviatt and McDougall, 1994).…”
Section: Review Of Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Transnational resources of entrepreneurs and employees foster a firm’s competitiveness (Mostafiz et al , 2020). Prior research suggests that international intrapreneurship might reinvigorate firms performance with innovation and change adaption in the domestic and external environments (Mubarik et al , 2020; Skarmeas et al , 2016). However, intrapreneurship studies in the international business context of the family firm in emerging markets have dropped behind those in Western settings (De Clercq and Zhou, 2014; Samiee et al , 2015; Urbano et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A very recent study by Mubarik et al (2020) examined the influence of human capital on the export performance of SMEs in the manufacturing sector of Pakistan. Using survey data from 586 manufacturing sector SMEs, they found that education and training have the greatest influence on the export performance of those firms.…”
Section: Empirical Studies On Human Capital Challengesmentioning
confidence: 99%
“…Particularly, when an organization finds that the performance of an internal service function is challenging to attain or costly to have in-house, outsourcing appears to be the feasible option. In the context of logistics management, third-party logistics (3PL) appears to be a cornerstone business strategy, which provides a multitude of business solutions from economies of scale, process flexibility to inventory reduction, optimum order cycle time and customer satisfaction (Mubarik, 2015; Aryee et al , 2019). The lynchpin for effective coordination between the organization and 3PL service providers is pivoted on the mutual benefits (Mubarik et al , 2019).…”
Section: Introductionmentioning
confidence: 99%